2015
DOI: 10.1177/1541931215591202
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Joint Resistance and Performance Degradation of the Extravehicular Mobility Unit Spacesuit

Abstract: Introduction:The primary objective of this pilot study was to characterize human performance degradations caused by the pressurized Extravehicular Mobility Unit Spacesuit (EMU). Method: This study assessed maximum strength (force) for elbow flexion/extension and shoulder abduction/adduction for three EMU suit conditions. Results: Statistically significant differences were observed between suit conditions during elbow flexion. Differences of practical significant were observed between suit conditions for mean p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This model is based on the upper body poses articulated without wearing a suit ("active poses"). However, it has been reported that wearing a space suit, particularly with the HUT and scye bearings, generally changes the patterns of upper-body poses [12], [13]. For example, the orientation of the scye bearings often results in subjects protracting their shoulders forward to a much greater extent even in a neutral pose than they would normally do when standing neutrally unsuited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This model is based on the upper body poses articulated without wearing a suit ("active poses"). However, it has been reported that wearing a space suit, particularly with the HUT and scye bearings, generally changes the patterns of upper-body poses [12], [13]. For example, the orientation of the scye bearings often results in subjects protracting their shoulders forward to a much greater extent even in a neutral pose than they would normally do when standing neutrally unsuited.…”
Section: Discussionmentioning
confidence: 99%
“…Proceedings of the 7th International Conference on 3D Body Scanning Technologies, Lugano, Switzerland, 30 Nov. -1 Dec. 2016 Thus, the right shoulder and upper extremity geometry can be constructed either of two different sets of vertex coordinates, namely the global coordinates and the coordinates estimated from the local-to-global transformation (Equation 4). To resolve the redundancy, a weighted average function (Equation 5) was applied to determine the final averaged coordinates ‫ܘ(‬ ୴ୣ୰ୟୣୢ ).…”
Section: Parametric Geometry Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…During EVAs, astronauts must wear gas-pressurized spacesuits to protect their bodies from the harsh conditions of space. Although these spacesuits are effective in keeping astronauts alive, they are known to severely limit human performance (i.e., by reducing joint mobility and strength) (Amick, Reid, England, & Rajulu, 2015; Gonzalez, Maida, Miles, Rajulu, & Pandya, 2002; Morgan, Wilmington, Pandya, Maida, & Demel, 1996; Reid et al, 2014) and pose a risk of musculoskeletal discomforts and injuries (Anderson et al, 2012; Anderson, Newman, & Welsch, 2015; Charvat, Norcross, Reid, & McFarland, 2015; Opperman, Waldie, & Newman, 2009; Scheuring, Mathers, Jones, & Wear, 2009; Strauss, 2004; Strauss, Krog, & Feiveson, 2005; Williams & Johnson, 2003).…”
Section: Introductionmentioning
confidence: 99%